2011
DOI: 10.1111/j.1752-0606.2011.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of a Model of the Process of Couples’ Forgiveness in Emotion-Focused Therapy for Couples

Abstract: This study explored how forgiveness unfolds in the context of emotion-focused couples therapy (EFT-C) in eight cases of women betrayed by their partners. Forgiveness was defined as a process involving the reduction in negative feelings and the giving out of undeserved compassion. This was measured by changes in the pre- and posttreatment scores on the Enright Forgiveness Inventory, the Unfinished Business Resolution Scale, and a single item directly asking respondents to indicate their degree of forgiveness. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…A key therapist action is thus to encourage the powerful partner to take actions that build relationship. Meneses and Greenberg () reported similar findings in a task analysis of forgiveness when women had been injured by their male partners. They stressed that “the ability of the injuring [powerful male] partner to tolerate and respond to the injured partner's anger and pain ultimately involves the injurer nondefensively accepting responsibility for the pain caused” (p. 498).…”
Section: Discussionmentioning
confidence: 63%
“…A key therapist action is thus to encourage the powerful partner to take actions that build relationship. Meneses and Greenberg () reported similar findings in a task analysis of forgiveness when women had been injured by their male partners. They stressed that “the ability of the injuring [powerful male] partner to tolerate and respond to the injured partner's anger and pain ultimately involves the injurer nondefensively accepting responsibility for the pain caused” (p. 498).…”
Section: Discussionmentioning
confidence: 63%
“…These results suggest that to move through impasses in EFT, it is important to be alert to potential attachment injuries and to provide adequate support to clients as they divulge and respond to perceived relationship betrayals. Makinen and Johnson's (2006) findings were corroborated some years later by Meneses and Greenberg (2011), who found in a study of eight couples in which the female partner had experienced a betrayal (four who forgave, four who did not forgive) that the process of forgiveness followed a similar series of steps that involved the expression and acceptance of heartfelt remorse and empathic responding. Findings on attachment injuries also support the notion that the resolution of attachment injuries might increase relationship satisfaction (Makinen & Johnson, 2006).…”
Section: Studies Focused On Client Variablesmentioning
confidence: 75%
“…In another study, Meneses and Greenberg (2011) found couples rated sessions containing the revealing of underlying emotions significantly more positively than randomly selected control sessions on a global measure of session outcome. In addition, following sessions in which underlying vulnerable emotions were revealed, those who witnessed their partners reveal felt significantly less troubled and significantly more understanding toward their revealing partners.…”
Section: Emotion-focused Therapymentioning
confidence: 95%